ANALISIS PENJATUHAN PIDANA REHABILITASI TERHADAP ANAK 0873 SEBAGAI PELAKU TINDAK PIDANA (Studi Putusan Mahkamah Agung Nomor 1298K/PID.SUS/2017). - Shara Kindly Febiola (Jurnal Hukum Adigama, 2021)
The law will never be separated from human life so if we discuss the law it will certainly be concerned with human life. A person who commits a criminal will definitely be subject to criminal sanctions in accordance with what criminal acts are committed and already written in an Act. Children who commit criminal acts have been regulated in an Act and General Review on Children, one of which is Law No. 11 of 2012 concerning the Juvenile Criminal Justice system. Minors who commit a criminal offense are usually due to the surrounding environment that is not good or parents who do not teach which children are good or bad may even be parents who make the child commit a criminal act. Children who commit criminal acts must still be legally protected and guaranteed because the child is still in the process of growth so that the child must be free from things that interfere with the child's growth.Children as a criminal offense in addition to being subject to prison penalties would be better if the child is processed through the Rehabilitation process. In its application, rehabilitation is applied to narcotics criminals but it would be better if the criminal investigation of rehabilitation is applied to children as other criminal offenders